Needs assessment: occupational health effort post in the informal sector in Pakpak Bharat District, Indonesia - Utami, Tri Niswati; Manik, Hubban Fathani; Acob, Joel Rey U; Aulia, Destanul; Sillehu, Sahrir (Journal of Community Empowerment for Health, 2025)
Introduction: The majority of workers in the informal sector have not received occupational health services. This study aims to explore health issues and assess the community's need for Occupational Health Services within the group of farmers.Methods: The activities are categorized into three parts: 1) Self-Assessment Survey (ASA). Data collection for the Self-Assessment Survey (SAS) activity is conducted using a questionnaire instrument, with a total of 10 farmer respondents collected to answer the questionnaire consisting of 5 assessments: work environment, personal protective equipment and safety, work performance, farmer’s health, and workplace hazards. 2) Village Community Assembly. Data collection for the Village Community Assembly activity is done through a Focus Group Discussion (FGD) with 35 study participants determined using a purposive sampling technique. 3) Establishment of occupational health effort posts. The implementation of the establishment of occupational health effort posts is done through a joint assembly with the village community and a facilitator team. Data analysis is conducted descriptively based on a Needs assessment. Musculoskeletal complaints, inadequate pesticide use for health requirements, and insufficient use of personal protective equipment were found.Results: The components of a needs analysis are based on considerations such as problem gaps, resource availability, support, and funding. The establishment of occupational health effort posts provides an appropriate platform for farmers to become acquainted with, prevent, early detect, and improve workers' health.Conclusion: Healthcare personnel needs to continuously provide support and health services through enhancement, guidance, and training to the farming community so that they can prevent and improve their health.